Improvement of complex treatment of patients with osteoarthritis combined with hypertension - Kuznecova, L P; Bondar, M V (Pain medicine, 2019)
Actuality: Among the diseases that significantly affect people, osteoarthritis (OA) takes 4th place in women and 8th in men. In both sexes older than 70 years, osteoarthrosis occurs in almost everyone, and in the last decade its prevalence has steadily increased. The social significance of OA is determined by the increase in disability, especially in older age groups, as well as by a sharp decline in the quality of life for this. Objective: To evaluate the efficacy of the therapy performed 12 months after initiation of treatment in patients with hypertension (GC) on the background of treatment with meloxicam at a dose of 7.5 mg/day and 80 and 160 mg/day. Material and methods: under supervision in an outpatient setting, there were 90 patients on the OA 1–2 stages, in combination with GC 2 degree, 2–3 degrees. The average age of patients with OA was 64.4 ± 7.5 years (the first group), patients with OA in combination with GC – 62.13 ± 8.2 years (second group), patients with OA in combination with GC and gastropathy due to admission NSAIDs (third group) – 64.81 ± 1.3 years. Disease duration in patients of the first group – (9.66 ± 4.7) years, in patients of the second group – (9.4 ± 6.0) years, in patients of the third group – (10.4 ± 5.6) years, respectively, the fourth group of comparison contained practically healthy persons. All patients complained of pain syndrome of varying degrees of severity. Patients in the first group received baseline therapy of meloxicam at a dose of 7.5 mg/day; patients in the second and third groups received meloxicam and antihypertensive drug (at a dose of 80 or 160 mg per day). Duration of treatment was 12 months. Results of the study and their discussion: according to the results, the positive effect of the use of meloxicam has led to a significant decrease in the severity of pain in the first, second and third groups according to the visual analogue scale (VAS): (27.8 %, 29.8 %, 25.4 %, p < 0.05) and the Lequesne index (27.1 % and 30.9 %, 26.4 %, p < 0.05), respectively. Conclusions: The tested scheme of treatment of patients with OA with the use of meloxicam indicates the efficacy and statistically significant reduction of pain syndrome, improvement of the functional state of the musculoskeletal system in patients with OA as well as with OA in combination with GC. 2.Also, the analgesic and anti-inflammatory effect of meloxicam and its positive effect on the clinical course of OA were revealed: joint pain decreased, functional capacity increased, general well-being and quality of life of patients improved. Prospects for further research: We consider it expedient to continue prospective surveillance of patients with the aim of further studying of the effect of meloxicam in patients with a comorbid disease. Conflict of Interest: There is no conflict of interest.